2019
DOI: 10.1590/1807-3107bor-2019.vol33.0117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MTA and Brazilian propolis on the biological properties of dental pulp cells

Abstract: The aim of this study was to evaluate the effect of mineral trioxide aggregate (MTA) and Brazilian propolis on the cell viability, mineralization, anti-inflammatory ability, and migration of human dental pulp cells (hDPCs). The cell viability was evaluated with CCK-8 kit after 1, 5, 7, and 9 days. The deposition of calcified matrix and the expression of osteogenesis-related genes were evaluated by Alizarin Red staining and real-time PCR after incubation in osteogenic medium for 21 days. The expression of infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
(36 reference statements)
2
7
1
Order By: Relevance
“…Peycheva [ 50 ] demonstrated that the expression of pro-inflammatory cytokines such as IL-1β, IL-6, TNF-α, IL-17A, IL-18, and INF-γ was significantly reduced in the gingival crevicular fluid isolated from adolescents with moderate gingivitis after receiving toothpaste containing propolis [ 50 ]. Similar observations on the effect of propolis in reducing the expression of pro-inflammatory cytokines were also made in studies investigating the effect of propolis on human periodontal ligament cells and human dental pulp cells and tissues [ 51 , 52 , 53 ]. In addition, propolis appeared to inhibit high glucose-induced NLRP3 inflammasome activation by downregulating the expression of NLRP3, caspase-1 and IL-1β mRNA and their associated protein levels [ 54 ].…”
Section: Resultssupporting
confidence: 71%
“…Peycheva [ 50 ] demonstrated that the expression of pro-inflammatory cytokines such as IL-1β, IL-6, TNF-α, IL-17A, IL-18, and INF-γ was significantly reduced in the gingival crevicular fluid isolated from adolescents with moderate gingivitis after receiving toothpaste containing propolis [ 50 ]. Similar observations on the effect of propolis in reducing the expression of pro-inflammatory cytokines were also made in studies investigating the effect of propolis on human periodontal ligament cells and human dental pulp cells and tissues [ 51 , 52 , 53 ]. In addition, propolis appeared to inhibit high glucose-induced NLRP3 inflammasome activation by downregulating the expression of NLRP3, caspase-1 and IL-1β mRNA and their associated protein levels [ 54 ].…”
Section: Resultssupporting
confidence: 71%
“…www.nature.com/scientificreports/ 96% purity, extracted by an enzyme digestion method from healthy unerupted human third molars were used. Transwell membranes with a pore diameter of 0.4 µm were used to mimic the absence of direct contact between the biomaterial and hDPSCs while allowing for soluble compounds from the biomaterials to reach the cells, similar to clinical conditions 17 . TCS-based cements are known to release Ca 2+ in varying concentration, depending on the cement composition.…”
mentioning
confidence: 99%
“…[28,29] Therefore, the ideal pulp capping material must be biocompatible, nontoxic, bactericide, anti-inflammation, antioxidative, and inducer of regenerative procedure in the damaged pulp tissue. [30] The application of natural bioactive ingredients attracts lots of attention in the regenerative medicine field. CUR is an ancient natural active ingredient, which accelerates healing procedures in different damaged organs.…”
Section: Discussionmentioning
confidence: 99%